Decoupling of optoelectronic properties from morphological changes in sodium treated kesterite thin film solar cells. (15th November 2018) - Andres, C.; Schwarz, T.; Haass, S.G.; Weiss, T.P.; Carron, R.; Caballero, R.; Figi, R.; Schreiner, C.; Bürki, M.; Tiwari, A.N.; Romanyuk, Y.E.
Highlights: Na is not detected at the CZTSe surface by XPS. Na concentration in the grain interior (30 ppm by APT) is lower than in the film (140 ppm by ICP-MS). Na improves efficiency, open-circuit voltage and fill factor of CZTSe solar cells. Na induces a shallow acceptor, which significantly increases the apparent doping concentration. Abstract: Sodium is typically used during the synthesis of kesterite thin films to enhance the performance of solar cells. As sodium tends to affect grain growth and morphology, it is difficult to analyse solely the electronic effects of sodium as dopant. To decouple the structural and electronic effects from each other, two processes were designed in this work to successfully incorporate sodium into a vacuum-processed Cu2 ZnSnSe4 absorber without changing the morphology. A thin layer of NaF is deposited before precursor deposition (Pre-NaF) or after absorber synthesis to undergo a post deposition treatment (NaF-PDT). While composition and distribution of matrix elements remain unchanged, the sodium concentration is increased upon sodium treatment up to 140 ppm as measured by inductively coupled plasma mass spectrometry. X-ray photoelectron spectroscopy showed that the surface composition was not altered. Within its detection limit, sodium was not present at the absorber surface. For a Pre-NaF sample measured with atom probe tomography a sodium concentration of 30 ppm was measured in a grain, suggesting that sodium might segregate at grain boundaries. The additional sodium content in the film leads to an increased acceptor concentration, which results in improved open-circuit voltage and fill factor.